Influences of Extreme Upwelling on a Coastal Retention Zone - Harvey, Julio B. J.; Ryan, John P.; Zhang, Yanwu (Frontiers in Marine Science, 2021)
Coastal retention zones occur in the lee of headlands and within bays of coastal upwelling environments. Because retention zones can concentrate and retain communities of coastal planktonic organisms that would otherwise be advected offshore by wind-driven transport, they are ecologically significant. While the consequences of these zones for plankton retention and recruitment have been examined, the degree to which they remain retentive under variable upwelling intensity is less well understood. This aspect of coastal plankton ecology was studied during 2012 in the retentive upwelling shadow of northern Monterey Bay, California. Environmental and biological data show that exceptionally strong upwelling can greatly diminish resident plankton populations in the upwelling shadow. Results indicate that wind-driven circulation, essential to primary productivity and the formation of retention zones, can surpass levels that allow accumulation and retention of plankton communities.